Abordagem para o design de jogos digitais terapêuticos - Souza, Paula Maia de (2018)
With the advancement of computational technologies, several areas of knowledge have enjoyed more and more of their benefits. One of the benefits that this technological advance has brought, within the area of health are the therapeutic digital games. They help hide the burden of the therapeutic tasks behind a fantasy world, raising motivation and adherence to therapy. However, the design of this category of games is more complex when compared to the design of conventional digital games. Because it is in a multidisciplinary context, it can be said that it is not enough just to have knowledge of game development, being also necessary to have knowledge about the pathology to be attended to and the domain that surrounds it. To date, no formalized methodology for the design of therapeutic digital games has been found in the literature that considers a multidisciplinary team and covers all stages of the design process. With this, this dissertation aims to formalize an semi-participatory approach for the design of therapeutic digital games, providin the participation of computer and health professionals in all stages of the design of a therapeutic game and facilitate communication between the stakeholders through well defined steps and activities. For this, a Systematic Review of the literature was initially undertaken to understand how existing therapeutic digital games were developed. Also as part of the baseline studies, a group of researchers who developed a game for patients with depression was studied, generating an account of experience. An initial version of the approach was presented to students of the Graduate Program in Nursing and applied by students of the Graduate Program in Computing, seeking to obtain feedback from these two groups in relation to the approach. After refinement of the approach, it was applied in the construction of a therapeutic digital game for the children and family attended by Hospital do Amor of the Barretos and evaluated by the professionals involved. The approach was named by SemTh, name inspired by the terms "Semio-participatory" and "Therapeutic Games". The SemTh is organized in four steps for the design, being: 1) Design Problem Clarification, where it is sought to understand the domain and propose the style of the game; 2) Interaction modeling, where the interactions of the game are modeled; 3) Design Materialization, where prototypes are created and the game is implemented; and 4) Evaluation, in this stage the game is evaluated by the team and by the end users. The evaluation of the approach was carried out in a qualitative way, through a questionnaire applied to professionals in the areas of computing and health, who participated in the game design for Hospital do Amor. The results of the evaluation pointed out that with the proposed approach it was possible to direct the computer team and empower the health team during the design of the therapeutic digital game.